2015
DOI: 10.1039/c5dt01817j
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, thermodynamic, kinetic studies and oxidase/antioxidant biomimetic catalytic activities of tris(3,5-dimethylpyrazolyl)borate Cu(ii) complexes

Abstract: A series of copper (II) ), have been synthesized and fully characterized. The substitution reaction of 1 with thiourea was studied under pseudofirst-order conditions as a function of concentration, temperature and pressure in methanol and acetonitrile as solvents. Two reaction steps that both depended on the nucleophile concentration were observed for both solvents. Substitution of coordinated methanol is about 40 times faster than the substitution of chloride. In acetonitrile, the rate constant for the displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…The non-electrolytic chloride ion in all complexes exhibits vibration bands, characteristics of the terminally-coordinated chloride ions. 33 Additionally, the three metal complexes all featured weak bands at around 442, 449, and 452 cm À1 , suggesting the existence of M-N bonds. 34 The thermogram TGA-DTG-DSC of FeC (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The non-electrolytic chloride ion in all complexes exhibits vibration bands, characteristics of the terminally-coordinated chloride ions. 33 Additionally, the three metal complexes all featured weak bands at around 442, 449, and 452 cm À1 , suggesting the existence of M-N bonds. 34 The thermogram TGA-DTG-DSC of FeC (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The effective magnetic moment for 2 , measured by the Evans method at room temperature in (D 6 )benzene, was 1.92 μ B . EPR experiments on 2 in frozen dichloromethane at 10 K provided only a broad spectrum, whereas several signals and the hyperfine splitting were resolved in spectra acquired in 2‐methyltetrahydrofuran, likely resulting from coordination of the solvent to give a five‐coordinate, square pyramidal geometry [15,69,70] . The spectrum is also best simulated in rhombic symmetry, with similar g values as To M CuBr, but smaller hyperfine splitting for g 1 =2.07 (A 1 =24 G) and larger splitting for g 3 =2.36 (A 3 =67 G).…”
Section: Resultsmentioning
confidence: 96%
“…The treatment of Me2 Tpm, K Me2 Tp, or i Pr TIC ligands with Cu II (NO 3 ) 2 ·3H 2 O afforded the corresponding known complexes Me2 TpmCu II (NO 3 ) 2 , 46 Me2 TpCu II (NO 3 ), 32 or i Pr TICCu II (NO 3 ) 2 in 85%, 90%, and 80% yields, respectively. A typical catalytic nitrite reduction experiment involved a mixture of the three LCu II complexes, NaNO 2 , and l -ascorbic acid in a 1 : 100 : 200 molar ratio, and these were stirred in 40 mL of CH 3 OH under a nitrogen atmosphere at room temperature (general conditions).…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31] The reactivities of Cu I -nitro complexes containing the neutral tripodal tris(3,5-dimethylpyrazolyl)methane ligand ( Me2 Tpm) or the anionic scorpionate hydrotris-(3,5-dimethylpyrazolyl)borate ( Me2 Tp) ligand for stoichiometric nitrite reduction were significantly influenced by the electronic density around the copper center. 27,32 The rate of NO 2 − reduction to NO (g) in the presence of the anionic ligand ( Me2 Tp, Scheme 1, Path 1) was faster at low temperatures (−30 °C) than that involving the neutral ligand ( Me2 Tpm) and the reactivity and NO (g) yield with the anionic ligand ( Me2 Tp) were better than those with the neutral ligand ( Me2 Tpm). Similarly, Fujii reported that the reactivities of Cu I -nitro complexes bearing tridentate nitrogen donor ligands follow the order Tpm < TIC (TIC = tris(4-imidazolyl) carbinols) due to the greater electron donating ability of imidazole relative to pyrazole.…”
Section: Introductionmentioning
confidence: 99%